2014
DOI: 10.1242/dev.099796
|View full text |Cite
|
Sign up to set email alerts
|

Novel cardiovascular gene functions revealed via systematic phenotype prediction in zebrafish

Abstract: Comprehensive functional annotation of vertebrate genomes is fundamental to biological discovery. Reverse genetic screening has been highly useful for determination of gene function, but is untenable as a systematic approach in vertebrate model organisms given the number of surveyable genes and observable phenotypes. Unbiased prediction of gene-phenotype relationships offers a strategy to direct finite experimental resources towards likely phenotypes, thus maximizing de novo discovery of gene functions. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…For example, median fold enrichment by DanioNet for the top 50 or top 100 candidates was over 45, which indicated that DanioNet is highly predictive for the genes involved in wide varieties of anatomical developmental processes. Recently, a classifier based on functional associations between zebrafish genes was used to predict the genes involved in each of the anatomical processes in zebrafish (41). However, this classifier was trained for only a fixed set of ZFA terms, whereas DanioNet-based prediction is not restricted to the predefined ZFA anatomical processes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, median fold enrichment by DanioNet for the top 50 or top 100 candidates was over 45, which indicated that DanioNet is highly predictive for the genes involved in wide varieties of anatomical developmental processes. Recently, a classifier based on functional associations between zebrafish genes was used to predict the genes involved in each of the anatomical processes in zebrafish (41). However, this classifier was trained for only a fixed set of ZFA terms, whereas DanioNet-based prediction is not restricted to the predefined ZFA anatomical processes.…”
Section: Resultsmentioning
confidence: 99%
“…Extrapolating to the set of 1047 human disease-associated genes with a yeast ortholog, complementation assays are within reach for ∼500 disease-associated genes, covering 10% of the ∼5000 disease-associated genes annotated in OMIM or HGMD. This fraction will of course be much higher when all other tractable model organisms are considered, e.g., zebrafish as a model for cardiac developmental disorders (Musso et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Both strategies have been demonstrated to provide high-quality gene-function predictions for (amongst others) H. sapiens 19,24 , M. musculus 17,48,49 , D. rerio 50 , and S. cerevisiae 51 . The union of these two CFNs were then taken as the single CFN used for this study, noting that while gene coverage overlap was high between the two networks, the gene-pair predictions were largely complementary (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%